Corrosion of Steel in High-Strength Self-Compacting Concrete Exposed to Saline Environment. (23rd April 2014) - Yousif, Hana A.; Al-Hadeethi, Farqad F.; Al-Nabilsy, Bashar; Abdelhadi, Amani N.
Abstract : A research work was carried out to investigate the effectiveness of high-strength self-compacting concrete (SF-R) in controlling corrosion of embedded steel. Reinforced concrete cylinders and plain cubes were subjected to 5% NaCl solution. Slump flow, J-ring, V-funnel, compressive strength, electrical resistance, and electrochemical tests were conducted. Corrosion resisting characteristics of steel were examined by monitoring corrosion potential, polarization resistance, corrosion currents, and Tafel plots. The relationship between corrosion current density and corrosion potential was established. Results were compared with characteristics of a grade 40 MPa reference concrete (R) and grade 70 MPa conventional self-compacting concrete (SP). Results indicated that at 270 days of exposure, the corrosion currents for steel in SF-R were 63- and 16-fold lower compared to those of steel in R and SP concretes, respectively. This concrete showed a considerable increase in electrical resistance and compressive strength of 96 MPa at 28 days of exposure. Relying on corrosion risk classification based on corrosion current densities and corrosion potentials, the steel in SF-R concrete is definitely in the passive condition. The splendid durability performance of steel in SF-R concrete linked to adorable self-compacting features could furnish numerous opportunities for future structural applications in severe environmental conditions.